2005
DOI: 10.1007/s10495-005-1901-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a non-antioxidant, dose-dependent role of α -lipoic acid in caspase-3 and ERK2 activation in endothelial cells

Abstract: Endothelial cell apoptosis contributes to atherosclerosis and may be exacerbated by oxidative stress. Results from clinical trials using antioxidant supplementation are equivocal and could be enhanced by antioxidants with additional non-antioxidant properties such as alpha -lipoic acid and alpha -tocopherol. The aim of this study was to investigate the effects of these antioxidants on cytoprotective pathways and endothelial apoptosis. Endothelial cells were incubated with alpha -lipoic acid and alpha -tocopher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 71 publications
3
14
0
1
Order By: Relevance
“…In support of our results, long time exposure to ALA results in increase of lipid peroxidation, mitochondrial damage and inhibition of glycogen synthesis [17,36]. Also, it has been shown that high dose of ALA could arrest cell cycles in some cells [35,55] or could provoke cell death through internucleosomal DNA fragmentation and caspase cleavage in numerous cancer cell lines [48,55,57]. Hence, it appears that high doses of ALA more than 100 uM are toxic for isolated preantral follicles.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In support of our results, long time exposure to ALA results in increase of lipid peroxidation, mitochondrial damage and inhibition of glycogen synthesis [17,36]. Also, it has been shown that high dose of ALA could arrest cell cycles in some cells [35,55] or could provoke cell death through internucleosomal DNA fragmentation and caspase cleavage in numerous cancer cell lines [48,55,57]. Hence, it appears that high doses of ALA more than 100 uM are toxic for isolated preantral follicles.…”
Section: Discussionsupporting
confidence: 83%
“…This observation may give explanation about our finding which why increasing of ALA concentrations results in decrease developmental competence of isolated follicles. In addition, as previous mentioned, high dose of ALA in numerous cancers cell lines could induce apoptosis [35,48,55,57] which explicates, high degeneration rate of follicles in the presence of high concentrations of ALA.…”
Section: Discussionmentioning
confidence: 57%
“…Most recent findings indicate that an ALA-VE combination increased endothelial levels of the antiapoptotic protein Bcl-2 with no significant changes in the levels of the pro-apoptotic protein Bax [44]. However, these beneficial effects seem to be dose-dependent [45]. Taken together, this evidence strongly suggests that combining ALA and VE is better than monotherapy.…”
Section: Synergism Between Lipoate and Tocopherolmentioning
confidence: 97%
“…On the other hand, the enhancement of MnSOD activity is not well explained. Modulation in the balance of Bcl-2/ Bax, anti-and pro-apoptotic proteins, seems to be also an important pathway to preserve antioxidant homeostasis [44,45].…”
Section: Synergism Between Lipoate and Tocopherolmentioning
confidence: 99%
“…Due to its potent antioxidant activity in vitro and in vivo, it is utilized as a preventive agent in diabetes mellitus, hypertension, and hepatic disorders (Bustamante et al 1998;Vasdev et al 2000;Packer et al 2001). Recent studies revealed that ALA induces cell cycle arrest in non-transformed cells and apoptotic cell death in several cancer cells (Marsh et al 2005;Wenzel et al 2005;Moungjaroen et al 2006). ALA is reduced to dihydro-ALA (DHLA) via mitochondrial dihydrolipoamide dehydrogenase, cytosolic glutathione reductase, and thioredoxin reductase (Slepneva et al 1995;Arner et al 1996;Bilska and Wlodek 2005).…”
Section: Introductionmentioning
confidence: 99%